A PROSPECTIVE STUDY OF SURGICAL MANAGEMENT OF FRACTURE NECK OF FEMUR IN ADULTS WITH CEMENTED BIPOLAR HEMIARTHROPLASTY - Y, SATYANARAYANA; C, SIVAKUMAR; D, RAVI PRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Displaced femoral neck fractures are frequently treated with bipolar hemiarthroplasties. There is little long-term data regarding bipolar hemiarthroplasty. This study aims to know the clinical efficacy of bipolar hemiarthroplasty in fractured neck femur in old age people. Patients are assessed postoperatively for pain, limp, and functional activities, and a Harris hip score is used to evaluate the results. Methods: This is a prospective study that included patients who underwent bipolar hemi replacement arthroplasty. A total 40 number of patients treated with bipolar prosthesis were assessed during our study. Both males and females were included in the study. We obtained all proper consent from patients during the study from a tertiary care hospital. Results: In this study, a sample of 20 patients with fractures of the neck of the femur with displacement, communication, and neck resorption above 50 years old were surgically treated with hemiarthroplasty using a bipolar endoprosthesis. Postoperatively, bipolar hemiarthroplasty allows for early mobilization, pain alleviation, and a high degree of activity while posing little risks. Conclusion: When compared to Austin Moore’s prosthesis, bipolar hemiarthroplasty had fewer complications, such as acetabular erosion and anterior thigh pain. As a result of these findings, we believe that bipolar hemiarthroplasty is the best treatment for intracapsular fracture neck femur.